Honey Bee (Apis mellifera) Queen Reproductive Potential Affects Queen Mandibular Gland Pheromone Composition and Worker Retinue Response - Rangel, Juliana; Böröczky, Katalin; Schal, Coby; Tarpy, David R. (PLOS ONE, 2016)
Reproductive division of labor is one of the defining traits of honey bees (Apis mellifera), with non-reproductive tasks being performed by workers while a single queen normally monopolizes reproduction. The decentralized organization of a honey bee colony is maintained in large part by a bouquet of queen-produced pheromones, the distribution of which is facilitated by contact among workers throughout the hive. Previous studies have shown that the developmental fate of honey bee queens is highly plastic, with queens raised from younger worker larvae exhibiting higher measures of reproductive potential compared to queens raised from older worker larvae. We investigated differences in the chemical composition of the mandibular glands and attractiveness to workers of “high-quality” queens (i.e., raised from first instar worker larvae; more queen-like) and “low-quality” queens (i.e., raised from third instar worker larvae; more worker-like). We characterized the chemical profiles of the mandibular glands of high-quality queens and low-quality queens using GC-MS and used the worker retinue response as a measure of the attractiveness to workers of high-quality queens vs. low-quality queens. We found that queen quality affected the chemical profiles of mandibular gland contents differently across years, showing significant differences in the production of the queen mandibular pheromone (“QMP”) components HVA and 9-HDA in 2010, but no significant differences of any glandular compound in 2012. We also found that workers were significantly more attracted to high-quality queens than to low-quality queens in 2012, possibly because of increased attractiveness of their mandibular gland chemical profiles. Our results indicate that the age at which honey bee larvae enter the “queen-specific” developmental pathway influences the chemical composition of queen mandibular glands and worker behavior. However, these changes are not consistent across years, suggesting that other external factors may play important roles in modulating queen quality.